Question

Asked Feb 11, 2020

1 views

Solve by substitution:

2x + y = − 7

5x + 3y = − 21

Step 1

Here,

2x + y = − 7 ….(1)

5x + 3y = − 21 ….(2)

Step 2

Derive the equation of y from equation (1)

2x+y = -7

y= -7-2x

Step 3

Substitute it in the equation (2).

...Find answers to questions asked by student like you

Show more Q&A

Q: Factor by grouping (sometimes called the ac-method). +x-2 First, choose a form with appropriate sign...

A: The given expression is

Q: Find the polynomial function with -1 as a zero of multiplicity 2, 1of multiplicity 2, and going thro...

A: If the root x=a has a multiplicity of n then one of the factor of function is (x-a)n.

Q: Darius is 4 years older than Shannon. In 9 years the sum of their ages will be 88. How old is Darius...

A: Let the age of Shannon is = x years So the age of Darius = (x+4) years

Q: Factor. (If the expression is nonfactorable over the integers, enter NONFACTORABLE.) b4 − 49a2

A: To factor the below expression

Q: Use the intermediate value theorem to show that f(x) = x^4 + 8x^3 −x^2 + 2 has a zero in I = [−1, 0]...

A: Given,

Q: Use the quadratic formula to solve the quadratic equation 2X2-5X-4=0

A: Given,

Q: Working on an explation of solution problem. Here is the question. Given: After 30% reduction the...

A: Click to see the answer

Q: this is a precalculus question

A: The initial height of the balloon is 131 meters. The balloon begins to ascend at a rate of 14 meters...

Q: Solve: 4x − 7y + 3z = 13x + y − 2z = 44x − 7y +3z =6

A: Click to see the answer